(untitled) (Al-Qamar, 2021)
In the contemporary age in Pakistan, the right to live is being taken away from human beings due to various reasons. Hundreds of young men and women are killed every year in Pakistan, whose only fault is that they have prioritized their own choice in the matter of marriage over the choice of their family. Why didn’t you agree to it? Apart from this, someone is killed based on suspicion. Moreover, these incidents not only cost the life of a person but also start a fight between two families. A few such incidents are mentioned during the Prophet’s Prophethood, in which he was prevented from being killed in the name of honor. In this paper, along with explaining the causes of honor killings, their solution will be presented in the light of Quran and Sunnah. Apart from this, the fact of honor killing will also be clarified, what is the perspective of Islam in this regard.